2016
DOI: 10.18632/oncotarget.13590
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-2 SNPs rs7342880 and rs4789936 are linked to risk of knee osteoarthritis in the Chinese Han Population

Abstract: This study aimed to investigate whether functional polymorphisms in the tissue inhibitors of metalloproteinase-2 (TIMP-2) gene are associated with susceptibility to knee osteoarthritis (OA) in the Chinese Han population. Six TIMP-2 single nucleotide polymorphisms (SNPs) were assayed using MassARRAY in 300 patients clinically and radiographically diagnosed with knee OA and in 428 controls. Allelic and genotypic frequencies were compared between groups. Logistic regression adjusting for age and gender was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The SNP rs4789936 localized in the intron of the gene, has been proved to be related to the knee osteoarthritis risk in Chinese Han population [ 31 ]. To the best of our knowledge, this is the first study to confirm the association between genetic variatins rs4789936 of TIMP-2 and the risk of LAA stroke in southern Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNP rs4789936 localized in the intron of the gene, has been proved to be related to the knee osteoarthritis risk in Chinese Han population [ 31 ]. To the best of our knowledge, this is the first study to confirm the association between genetic variatins rs4789936 of TIMP-2 and the risk of LAA stroke in southern Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…A total of six SNPs (i.e., rs2277698, rs2009196, rs7342880, rs11654470, rs2003241, rs4789936) were selected for further genotyping. These SNPs were analyzed in vascular diseases or other diseases, such as the breast cancer [ 25 ], abdominal aortic aneurysm [ 26 ], knee osteoarthritis [ 31 ]. Genomic DNA was extracted from peripheral blood of cases and controls using the GoldMag whole blood genomic DNA purification kit (GoldMag Co. Ltd., Xi’an, China), as recommended by the manufacturer's instructions [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results also revealed a significantly differing distribution of TIMP-1 expression between Ta and T1 stage specimens, and the authors concluded that urinary TIMP-1 can be a useful, non-invasive biomarker that may serve as a decision making tool for bladder cancer disease management ( 101 ). Three SNPs were reported in TIMP-1, including 261 C->T, 328+16 C->T and 372 T->C, ( 102 ), while six SNPs were reported in TIMP-2, including rs2277698 T->C, rs2009196 C->G, rs7342880 A->C, rs11654470 C->T, rs2003241 C->T, rs4789936 T->C ( 103 ).…”
Section: Metalloproteinase Familymentioning
confidence: 99%